Exploring Capitalism in the Economy of Early Modern Gujarat: The Structure and Organization of Textile Production and the Market in Surat in the Eighteenth Century - Ghulam A. Nadri (Historia Crítica, 2023)
Objective/Context: This study has two main goals. First, it explores the structural and organizational dynamics of the textile industry and the market in early modern India, eighteenth-century Gujarat in particular. In this context, the paper also examines how the ascendancy of the English East India Company in the political economy of Western India and the region’s transition to a colonial economy impacted the industry, the market, and the relationship between weavers and merchants. Methodology: This paper draws on the literature on textile production and trade, as well as on capitalism in early modern and colonial India, and uses evidence about Gujarat from the records of the English and Dutch East India Companies. Originality: This paper argues that the relationship between weavers and merchants in Surat/Gujarat was dynamic, complementary, and at times, contentious. None of them was able to dominate the relationship, and the English East India Company could not substitute a coercion-based production relation for a market-based one. Conclusions: The dynamics—such as product specialization and innovation, division of labor, the contract system, and forward buying—point to the existence of commercial capitalism in the textile economy. The paper also argues that because of the extraordinary diversity of people engaged in the industry and their varying professional and transactional experiences, it is relevant to recognize that commercial capitalism represents a mode of production that co-existed with others in the economy.